(untitled) (Journal of Advanced Research in Social Sciences, 2023)
There is enormous literature citing the importance of workplace spirituality. This article focuses on the concept of spirituality and to understand its role in workplace using narrative review methodology. A few definitions of spirituality and workplace spirituality are examined and common features in those definitions are identified. Existing literature on why spirituality at workplace is vital is reviewed. The arguments against and for the workplace spirituality are expressed. The core purpose of the paper is to understand the concept of spirituality and how it manifests at the workspace, whether it should be nurtured or discouraged with respect to its impact on the employee and the organisation (consequentialist framework) or because of the individuals search for meaning, purpose, transcendence and divinity (spiritual-philosophical framework).The result indicate that spiritual-philosophical framework should be the primary reason for organisations to promote workplace spirituality. The reasons for, and implications of the same are discussed.